2014
DOI: 10.1111/mec.12776
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic habitats and cryptic diversity: unexpected patterns of connectivity and phylogeographical breaks in a Mediterranean endemic marine cave mysid

Abstract: The marine cave‐dwelling mysid Hemimysis margalefi is distributed over the whole Mediterranean Sea, which contrasts with the poor dispersal capabilities of this brooding species. In addition, underwater marine caves are a highly fragmented habitat which further promotes strong genetic structuring, therefore providing highly informative data on the levels of marine population connectivity across biogeographical regions. This study investigates how habitat and geography have shaped the connectivity network of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 90 publications
1
47
0
3
Order By: Relevance
“…Marine caves constitute fragmented habitats (Harmelin et al, 1985), especially in the eastern Mediterranean, an area presenting heterogeneity in abiotic conditions, seascape, and coastline geomorphology. These features may function as phylogeographic breaks, influencing isolation and triggering speciation processes, as shown by Rastorgueff et al (2014). The vast majority of marine caves recorded in the Aegean ecoregion are located in insular areas (Giakoumi et al, 2013), possibly indicating a higher level of isolation (Bibiloni et al, 1989).…”
Section: Conclusive Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Marine caves constitute fragmented habitats (Harmelin et al, 1985), especially in the eastern Mediterranean, an area presenting heterogeneity in abiotic conditions, seascape, and coastline geomorphology. These features may function as phylogeographic breaks, influencing isolation and triggering speciation processes, as shown by Rastorgueff et al (2014). The vast majority of marine caves recorded in the Aegean ecoregion are located in insular areas (Giakoumi et al, 2013), possibly indicating a higher level of isolation (Bibiloni et al, 1989).…”
Section: Conclusive Remarksmentioning
confidence: 99%
“…Bailey, 1969;Hayward, 1974; ranean areas and showed that sponges exhibit clear biogeographic patterns, thus underlining the need to conserve this habitat across the Mediterranean in order to ensure representativeness. Rastorgueff et al (2014) studied cave mysid populations throughout the northern Mediterranean and revealed contrasting patterns of genetic structuring between the western and eastern parts of the basin, which could be attributed to the presence of phylogeographic breaks. Spatial heterogeneity among and within ecoregions is considered a crucial factor that needs to be taken into account in future conservation plans (Giakoumi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…1a & b) forms mobile swarms above the sediment that number several hundreds of thousands of individuals ( Fig. 1a; Rastorgueff et al 2014). It reaches the entrance of caves at night to feed mostly on phytoplankton-derived material inside and outside the bottom of caves (Rastorgueff et al 2011).…”
mentioning
confidence: 99%
“…H. mariannae therefore appears to experience a more fragmented habitat than H. margalefi. Phylogeographic studies have revealed the strong population genetic structure of H. margalefi and have shown a remarkable connectivity between populations of H. mariannae, even at the scale of the Mediterranean Sea Rastorgueff et al 2014), which is attributed to the differences in their ability to use cavities as habitats. Since H. margalefi forms large swarms, it can only be found in large caves.…”
mentioning
confidence: 99%
“…Os resultados da tabela 10 representam os valores obtidos para diversas mensurações em cada estrutura encontrada. Trabalhos atuais têm demonstrado que espécies descritas como generalistas (com alta plasticidade fenotípica) ampla distribuição geográfica possuem claras evidências de se tratarem de espécies crípticas (Zhou et al, 2012;Rastorgueff et al, 2014;Chen et al, 2017) morfologicamente semelhantes, apenas análises moleculares (filogenia mitocondrial) têm tornado possível a separação destes táxons e demonstrado que barreiras geográficas e instabilidade climática têm um papel importante na especiação destes grupos. O final do Ediacarano foi marcado por eventos geofísicos intensos como os descritos na introdução.…”
unclassified